Buccal Mucosal Graft in Repeat Urethroplasty - Mehrsai, Abdorasol; Djaladat, Hooman; Sina, Alireza; Salem, Sepehr; Pourmand, Gholamreza (Urology Journal, 2009)
Â Introduction: Our aim was to evaluate the efficacy of a tubed buccal mucosal graft in repeat urethroplasty for patients with urethral stricture and failed previous operations. Materials and Methods: Ten patients (aged 12 to 47 years) with urethral stricture were entered into the study. All had a history of failed previous urethroplasties, and 5 had failed internal urethrotomies too. Repeat urethroplasties were performed by excising the fibrous tissue around the stricture; buccal mucosa was then harvested from the inner cheek, made into graft tubing, and interposed into the defect. The patients were followed at 1, 6, and 12 months. Results: The procedure was technically successful in all the patients. The mean operative time was 150 minutes. The stricture sites were in the posterior urethra in 8 and the anterior urethra in 2 patients. The mean urethral defect length was 4.9 cm. The primary etiology was pelvic fracture in 7 patients. Strictures recurred postoperatively in 3 patients, all of whom had a urethral defect longer than 5 cm, and 2 of whom had more than 1 previous failed urethroplasties (compared with 1 out of 7 in the successful cases). Urinary flow rate increased significantly (from 0 to 10.4 Â± 7.33 mL/s) postoperatively (P = .018). Longer strictures produced signifcantly poorer graft urethroplasty outcomes (P = .001). Conclusion: Urethroplasty with buccal mucosal grafts is tough, resilient, easy to harvest, and it leaves no scar. It appears to be an optimal substitute for anterior and posterior urethral strictures longer than 3 cm.